BUTIR-BUTIR PEMIKIRAN DALAM SEJARAH INTELEKTUIL DAN PERKEMBANGAN AKADEMIK HUKUM DAN EKONOMI - Sugianto, Fajar (DiH: Jurnal Ilmu Hukum, 2014)
This writing is intended to convey the basic ideas of what has come to be known as Law and Economics, or also commonly called Economic Analysis of Law. The subject areas of concern are central ones for the origins of law and economics which have been contributed by â€œthe Founding Fathersâ€, namely, David Hume, Adam Ferguson, Adam Smith, Jeremy Bentham, Ronald Coase, Henry Simons, Gordon Tullock, Richard Posner, and Steven Shavell. Because the main object is to present the fusion of horizons between law and economics, this writing had excluded formal economic analysis as well as detailed discussion of most legal area. Like many most accepted theories of jurisprudence, Law and Economics also look to reveal the crucial and definitive aspects of the foundation of law.Keywords: Fusion of horizons, academic recognition, Law and Economics.